Comparison between plasma electrolytic oxidation coating and sandblasted acid-etched surface treatment: Histometric, tomographic, and expression levels of osteoclastogenic factors in osteoporotic rats - Momesso, Gustavo Antonio Correia [UNESP]; de Souza Santos, Anderson Maikon [UNESP]; Fonseca e Santos, João Matheus [UNESP]; da Cruz, Nilson Cristino [UNESP]; Okamoto, Roberta [UNESP]; Ricardo Barão, Valentim Adelino; Siroma, Rafael Shinoske; Shibli, Jamil Awad; Faverani, Leonardo Perez [UNESP] (MDPI, 2020)
Plasma electrolytic oxidation (PEO) has been a promising surface coating with better mechanical and antimicrobial parameters comparing to conventional treatment surfaces. This study evaluated the peri-implant bone repair using (PEO) surface coatings compared with sandblasted acid (SLA) treatment. For this purpose, 44 Wistar rats were ovariectomized (OVX-22 animals) or underwent simulated surgery (SS-22 animals) and received implants in the tibia with each of the surface coatings. The peri-implant bone subsequently underwent molecular, microstructural, bone turnover, and histometric analysis. Real-time PCR showed a higher expression of osteoprotegerin (OPG), receptor activator of nuclear kappa-B ligand (RANKL), and osteocalcin (OC) proteins in the SLA/OVX and PEO/SS groups (p < 0.05). Computed microtomography, confocal microscopy, and histometry showed similarity between the PEO and SLA surfaces, with a trend toward the superiority of PEO in OVX animals. Thus, PEO surfaces were shown to be promising for enhancing peri-implant bone repair in ovariectomized rats.
Keywords: Anodic films; Bone; Experimental; Implants; Oxide coating